PROFIL PEMECAHAN MASALAH PENGGUNAAN TEOREMA HERON UNTUK MNENTUKAN LUAS DAERAH SEGITIGA PADA SISWA KELAS XI MIA 1 SMA NEGERI 3 PALU: Profile of Problem Solving Using Heron's Theorem to Determine The Area of A Triangle on Students in Class XI MIA 1 SMA Negeri 3 Palu - Bendelina Juwita Pasaung; Sudarman Bennu; Baharuddin Paloloang (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a problem solving profile using Heron's theorem in determining the area of a triangle. This research is a qualitative research with the subject of three students of class XI MIA 1 SMA Negeri 3 Palu, each one student with high, medium and low math ability. Subject selection for the classification of students' abilities using the standard deviation. Data were collected by observation, student answers and interviews. The problem solving used in this study uses the Polya problem solving step. The results of this study indicate that: (1) students with high, medium and low math abilities understand the problem by identifying information and command sentences on the task to determine what is known and asked. (2) students with high math abilities and making problem-solving plans use ???? = √????(???? − ????)(???? − ????)(???? − ????), while students with low math skills use ????=(a+b+c)/2. (3) high-ability students carry out the problem-solving plan according to the plan correctly, capable students are carrying out according to the plan but are wrong in solving it and low-skill students are wrong in carrying out the plan because the problem-solving plan made is not right. (4) high-ability students and are reviewing the results of their work from the beginning but moderately capable students are not aware of any mistakes, and low- skilled students do not re-examine the results of their work.